Advanced Introduction to Cultural Economics - Towse, Ruth (Cheltenham Edward Elgar Publishing Ltd., 2014)
Written by an internationally renowned expert in the field, Professor Ruth Towse, this book presents a comprehensive yet concise introduction to cultural economics. She covers a broad range of topics in the arts and cultural industries, using the tools of economics to explain their supply and demand, production and consumption.
​1. About Cultural Economics -- 2. Cultural Economics and Cultural Policy -- 3. Performing Arts -- 4. Museums and Built Heritage 5. Artists, the Art Market and Artists’ Labour Markets -- 6. The Creative Economy -- 7. Copyright -- 8. Broadcasting Music and Film Industries -- 9. Festivals, Cities of Culture, Creative Clusters and Economic Impact 10. Conclusion Index
Includes bibliographical references (pages 134-146) and index
Keywords: Production; PERFORMING ARTS; CULTURE; ECONOMIC ASPECTS; CULTURAL INDUSTRY